Development of Power Electronics Based Test Platform for Characterization and Testing of Magnetocaloric Materials. (31st January 2015) - Elamalayil Soman, Deepak; Loncarski, Jelena; Gerdin, Lisa; Eklund, Petter; Eriksson, Sandra; Leijon, Mats
Abstract : Magnetocaloric effects of various materials are getting more and more interesting for the future, as they can significantly contribute towards improving the efficiency of many energy intensive applications such as refrigeration, heating, and air conditioning. Accurate characterization of magnetocaloric effects, exhibited by various materials, is an important process for further studies and development of the suitable magnetocaloric heating and cooling solutions. The conventional test facilities have plenty of limitations, as they focus only on the thermodynamic side and use magnetic machines with moving bed of magnetocaloric material or magnet. In this work an entirely new approach for characterization of the magnetocaloric materials is presented, with the main focus on a flexible and efficient power electronic based excitation and a completely static test platform. It can generate a periodically varying magnetic field using superposition of an ac and a dc magnetic field. The scale down prototype uses a customized single phase H-bridge inverter with essential protections and an electromagnet load as actuator. The preliminary simulation and experimental results show good agreement and support the usage of the power electronic test platform for characterizing magnetocaloric materials.